Investor Subjectivities in Melbourne's High Cost Housing Market. Issue 1 (1st January 2022) - Gorter, Tamlin; Jacobs, K.
ABSTRACT: The political economy of housing in Australia is in flux; households increasingly engage in the housing market as a way to manage social and financial risks. Addressing a lack of empirical research on household decision-making, we interviewed 40 owners and renter households in Melbourne. Participants understood the role of housing as a financial asset; this was enacted through their adoption of the position of a neoliberal investor subject engaged in speculative investment and rational calculation of risks and rewards. Renters were conscious of living in their landlord's investment. However, some participants also articulated active resistance to speculative investment in the housing market, and their commitment to the use value of housing and other meanings of home. This examination of the feelings and practices of participants within the housing market provided new insights into the ways that neoliberal ideology and financialization processes are currently shaping Australia.